IMPROVEMENT OF SOCIOLINGUISTIC COMPETENCE IN TEACHING THE RUSSIAN LANGUAGE - Alimsaidova Sayyora (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article reveals the main aspects of using the language of a particular language community in mastering the sociolinguistic rules of speech communication that characterize this society, as well as understanding the impact of social factors on the speech behavior of communication participants.